2016
DOI: 10.1002/hed.24371
|View full text |Cite
|
Sign up to set email alerts
|

Human olfactory stem cells for injured facial nerve reconstruction in a rat model

Abstract: This study suggests that olfactory stem cells may be used as a potent cellular therapy for accelerating the regeneration of peripheral nerve injuries. © 2016 Wiley Periodicals, Inc. Head Neck 38: E2011-E2020, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
8
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 64 publications
(156 reference statements)
4
8
0
2
Order By: Relevance
“…Total nerve laceration usually occurs as a result of trauma, tumour excision, or iatrogenic etiologies. Although peripheral motor nerves have regeneration capacity, full healing is not achieved if total nerve laceration is present [Batioglu-Karaaltin et al, 2016]. The outcomes of end-toend anastomosis are not always satisfactory because of poor axonal regeneration and synkinesis [Chu et al, 2018;Edizer et al, 2019].…”
Section: Discussionmentioning
confidence: 99%
“…Total nerve laceration usually occurs as a result of trauma, tumour excision, or iatrogenic etiologies. Although peripheral motor nerves have regeneration capacity, full healing is not achieved if total nerve laceration is present [Batioglu-Karaaltin et al, 2016]. The outcomes of end-toend anastomosis are not always satisfactory because of poor axonal regeneration and synkinesis [Chu et al, 2018;Edizer et al, 2019].…”
Section: Discussionmentioning
confidence: 99%
“…показали, що застосування нейрогенних стовбурових клітин справляє позитивний ефект не тільки при гострій травмі нерва, а і при хронічній денервації, що підтверджувалося електрофізіологічними та морфологічними методами [9,85]. Застосування їх обмежується тому, що використання нейральних стовбурових клітин при різних видах травми ПН супроводжується високим ступенем утворення нейробластом [86], тому увагу дослідників привернули більш диференційовані клітини, а саме клітини нюхової цибулини [87]. Виявлено, що вони здатні продукувати речовини, які стимулюють регенерацію ПН: FGF, NGF, BDNF, GDNF, білки екстра целюлярного матриксу [88,89].…”
Section: джерела і види стовбурових клітин для відновлення периферичнunclassified
“…There are studies using adult, embryo and fetal stem cells for the regeneration of nerve damage. Many subtypes of these stem cells, such as bone marrow, mesenchymal and neural stem cells have been used for regeneration in peripheral nerve damage [2,9,13,14].In previous years, there are animal studies carried out using many kind of stem cells in the FP that reported good results [15][16][17][18][19][20][21][22]. There is no research in the literature about the effects of fetal brain tissue-oriented mesenchymal stem cells (FBTMSC) on facial nerve damage.…”
Section: Introductionmentioning
confidence: 99%